Integrasi Model Project Based Learning (PjBL) dan Etnobiologi dalam Meningkatkan Literasi Sains Mahasiswa - Dina Aulial Husna; Efriana Jon; Nana Sutrisna; Novita Amri; Al Ikhlas; Abdi Sakti Walenta (Journal on Education, 2024)
Science literacy is an important ability that must be possessed by students in the 21st century. However, several studies show that the science literacy of students in Indonesia still needs to be improved. One approach that is considered effective is through the integration of Project Based Learning (PjBL) and ethnobiology models. This study aims to examine the effectiveness of the integration of PjBL and ethnobiology models in improving students' science literacy. The research method used was a pseudo-experiment with a pretest-posttest control group design. The sample consisted of two classes of students, one class as an experimental group that applied the integration of PjBL and ethnobiology, and one class as a control group that applied conventional learning. The results showed that the experimental group that applied the integration of PjBL and ethnobiology had a higher increase in science literacy compared to the control group. Further analysis revealed that the integration of PjBL and ethnobiology had a significant effect on improving students' science literacy, both in the aspects of knowledge, thinking skills, and scientific attitudes. The findings of this study imply that the integration of PjBL and ethnobiology can be an effective learning strategy to improve students' science literacy. The implication of the results of this study is the need for the implementation of innovative learning approaches that connect science with local wisdom and contextual problems in order to improve the quality of science education in higher education.